2014 IEEE/RSJ International Conference on Intelligent Robots and Systems 2014
DOI: 10.1109/iros.2014.6942810
|View full text |Cite
|
Sign up to set email alerts
|

Remote vertical exploration by Active Scope Camera into collapsed buildings

Abstract: Remote robotic explorations for collapsed buildings in a severe disaster are demanded. However, rescue robots cannot approach the rubble due to safety risks. This study proposes a remote vertical exploration system for collapsed buildings with a robotic inspection system hoisted by a crane. An Active Scope Camera (ASC) has many advantages for the vertical exploration such as a light and flexible continuum body to produce distributed driving forces. The purpose of this paper is to confirm the feasibility of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…We implemented temporal smoothing over confidence values, which helped to obtain cleaner results on test footage and footage from a serpentine robot platform (Fukuda, Konyo, Eijiro, & Tadokoro, 2014). However, in integrating the system with the cyber-enhanced canine suit, we found that SAR dogs' often high pace and wild movement (especially in comparison to slow robotic platforms) limits how much of such temporal smoothing can be applied, as it assumes high similarity between subsequent frames.…”
Section: Thresholdingmentioning
confidence: 99%
“…We implemented temporal smoothing over confidence values, which helped to obtain cleaner results on test footage and footage from a serpentine robot platform (Fukuda, Konyo, Eijiro, & Tadokoro, 2014). However, in integrating the system with the cyber-enhanced canine suit, we found that SAR dogs' often high pace and wild movement (especially in comparison to slow robotic platforms) limits how much of such temporal smoothing can be applied, as it assumes high similarity between subsequent frames.…”
Section: Thresholdingmentioning
confidence: 99%
“…The body was rotated at 90 • after installing each microphone in order to avoid having all microphones obstructed by the ground. This robot moves forward by a mechanism in the same way as that of the Active Scope Camera robot [1]: the entire surface of the robot is covered by cilia, and the robot moves forward by vibrating them. This vibration is generated by seven vibration motors installed in the robot ( Fig.…”
Section: Design Criteriamentioning
confidence: 99%
“…Hose-shaped rescue robots have been developed for gathering information in narrow spaces under collapsed buildings where humans or animals cannot enter [1][2][3]. They have thin, long, and flexible bodies and have selflocomotion mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A robotic system that allows the inspection of narrow spaces while keeping a constant diameter all along the device is the active scope camera [16]. This robot has been tested in disaster situations with debris and has shown good performance in adapting to its surroundings.…”
Section: Introductionmentioning
confidence: 99%